Gaining in-demand skills in the ESP classroom: a case study in Oman - Victoria Tuzlukova; Peter Heckadon (English, 2020)
The most recent trends in education emphasize the importance of its strong focus on the learner’s job-readiness, a convergence of education with the world of work, and its adaptation to the needs of the learner and the employer. Ascribable to its far-reaching partnership with 21st-century educational thinking, demand-driven education, and planning for the future, the English for Specific Purposes (ESP) classroom is no exception to this, seeing modifications and adaptations in its search for a deeper understanding of the reliable skill set introduction and development. While debating current global and local issues, changes, and challenges in the broad area of ESP, this paper focuses on Omani tertiary education students’ understanding of in-demand 21st-century skills and their development in the dimensions of these skills. The discussion is anchored in the personal feedback of students enrolled in the English for Business course offered by the Centre for Preparatory Studies at Sultan Qaboos University in Oman. In terms of future employability, students were asked to rate twenty-three skill areas and how these skill areas were covered in the course in bilingual English and Arabic questionnaire administered online. The results demonstrate students’ understanding of the importance of 21st-century skills for future employability. They also show that effective in-demand skill instruction requires teacher initiative in the enhanced incorporation of learner-centered teaching approaches and more language learning activities and tasks with a focus on interactive and experiential instruction. This involves a synthesis of best practices in integrated language skills with a special focus on speaking, the application of different innovative tools and techniques of teaching, and enhancement of positive attitudes toward aligning skill areas, with an emphasis on idea development, content knowledge, critical and creative thinking.